Vivo Extraction and Forensic Profiling of Toxic Plant Seeds Constituents via Gas Chromatography Mass Spectrometry - Kiran Kumari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Plants are the outline of human society. Although only some of the chemical components present in the plant are equally crucial for the human body, Sometimes, these compounds accumulate in human body tissues, produce highly toxic elements, and sometimes cause death. Forensic experts need to have a good knowledge of these phytochemicals while performing analysis to interpret toxicology cases. The present study has devised a new extraction protocol for extracting the bioactive components of toxic plant seeds from mice's viscera. The calculated LD50 doses of toxic seed extracts of Jatropha curcus, Datura inoxia, Thevetia neriifolia, Ricinus communis, and Abrus precatorius were given to the mice. A new extraction method was developed for the extracts of the bioactive components after slightly modifying the previously practiced ammonium sulfate method. Gas chromatography-mass spectrometry aids in the conclusive identification of constituents extracted from biological material. Most of the identified compounds were found in the metabolite forms of the phytoconstituents. This new and modified extraction procedure created valid results that helped generate a database of many toxic plant seed constituents and metabolites for its forensic utility.